All landscape is collaborative: re-mobilizing care and concern on a damaged planet. Issue 3 (3rd July 2022) - Wergin, Carsten
Abstract : This article looks at landscapes as 'collaboratories' in which the dynamic relationship between socio-ecological crisis and sociocultural transformation can be harnessed to shape a more sustainable future. The Anthropocene has dramatically changed scientific inquiry, from a demand to find responses to global environmental degradation to a straightforward acknowledgment of existential changes that have become inevitable. There is therefore a need for more interdisciplinary and public engagement that can enhance local and global capacity building, social innovation and resilience. This article presents the notion of 'landscape collaboratoria' as a theoretical strategy for doing so through engagement with landscapes. It advocates for the use of empirical data to conceptualize manifestations of heritage and biodiversity in landscapes as well as knowledge production about them. Drawing on illustrative examples, the text suggests a more integrative approach that views landscapes as 'collaboratoria' supporting both the preservation of heritage and the protection of biodiversity.